Review of preparation methods of pyrouric acid - Ning ZHANG (Hebei University of Science and Technology, 2021)
With the advance of ecological civilization construction,the domestic demand for green environmental protection is also higher and higher.As an important chemical intermediate,the traditional preparation method of pyrouric acid has some problems such as environmental pollution,so it is urgent to study and popularize the new preparation method.The process and characteristics of solid phase and liquid phase methods for the preparation of pyrouric acid were systematically reviewed.The problems of traditional preparation methods such as bad operating environment,high energy consumption and not up to the standard of environmental protection were elucidated.The development prospect of preparation methods of pyrouric acid was also prospected.It is pointed out that further research on the preparation of pyrouric acid can be carried out in the following aspects.1)It is necessary to carry out research on rotary kiln and fluidized bed equipment,gradually [JP2]replace tunnel kiln,[JP]realize the upgrading of technical equipment,and overcome the shortcomings of traditional solid phase method;2)In order to lay a foundation for industrial production,the selection and recovery of solvent system in liquid phase method should be deeply explored,and the research of liquid phase method in small scale and scale up in pilot scale should be strengthened;3)The raw material source,product yield and production cost of the new preparation method should be systematically and deeply studied in order to realize large-scale production.